Paramphibambusa guizhouensis sp. nov. (Cainiaceae, Xylariales) a bambusicolous ascomycete from Guizhou, China - Zeng, Lina; Lu, Changtao; Li, Qirui; Khurshid, Rubab; Habib, Kamran; Lu, Pingzhu (Phytotaxa, 2025)
A novel species of family Cainiaceae, Paramphibambusa ghizhouensis is introduced based on morphological characteristics and phylogenetic analyses of ITS and LSU sequence data. Phylogenetically, the new taxon forms a well-supported clade within Paramphibambusa, sister to P. bambusicola. It is characterized by larger ascomata (635–850 × 430–600 µm), smaller asci (130–210 × 8.1–14.4 µm), and smaller ascospores (18.4–29.3 × 4.8–7.5 μm) with rounded ends, which differentiate it from its sister species, P. bambusicola. A comprehensive description, illustrations, and a phylogenetic tree are provided to confirm the systematic placement of this new species.